Electric Field Induced Room Temperature Null to High Spin State Switching: A Computational Prediction. Issue 4 (1st February 2019) - Amorim, Carlos O.; Amaral, João S.; Gonçalves, João N.; Amaral, Vítor S.
Abstract: BaTiO3 is a well‐known ferroelectric material, with an electric field‐induced coupled electrical/structural transition from a cubic to a tetragonal lattice above room temperature. Via DFT calculations, the magnetic properties of an Fe monolayer sandwiched between bulk‐like BaTiO3 are explored, showing how the magnetic moment of each Fe atom is switched from a null spin to a high spin (2 μB per Fe) state when the BaTiO3 structure changes from cubic to tetragonal. This effect occurs in an optimized range of interatomic distances at the interface, allowing the design of an above‐room temperature binary, electric field write/magnetic read device. Abstract : DFT simulations show that, under appropriate conditions, a Fe monolayer sandwiched between bulk‐like BaTiO3 presents a null spin (0 μB per Fe) to high spin (2 μB per Fe) transition when the BaTiO3 structure changes from cubic to tetragonal, due to changes in the crystal field at the Fe positions. This effect may be controlled thought an electric field induced first‐order ferroelectric phase transition.